Inhuman Nature - Cohen, Jeffrey Jerome (punctum books, 2014)
Gathering into lively conversation scholars in medieval, early modern and object studies, Inhuman Nature explores the activity of the things, forces, and relations that enable, sustain and operate indifferently to us. Enamored by fictions of environmental sovereignty, we too often imagine "human" to be a solitary category of being. This collection of essays maps the heterogeneous and asymmetrical ecologies within which we are enmeshed, a material world that makes the human possible but also offers difficulties and resistance. Among the topics explored are the futurity that inheres in storms and wrecks, wood that resists its burning or offers art and dwelling, hymns that implant themselves like viruses, the ontology of everyday objects, the seep and flow of substance, the resistant nature of matter, the dependence of community upon making things public, and the interstices at which nature and culture become inseparable. Tinker as you will.